Development of Educational Professional Learning Materials Based On Cultural Discourse In Higher Education - Yulastri, Weni; Zulfa, Zulfa; Juliardi, Budi; Zulkifli, Zulkifli; Rudagi, Reindy; Yulmiati, Yulmiati (ppjbsip, 2023)
The Educational Profession course is crucial to teacher training, however transitioning to independent learning curricula is difficult. Teaching resources that fit the changing educational landscape are a big challenge. This study proposes incorporating cultural discourse into educational professional teaching resources to meet independent learning curricular requirements. To create these innovative instructional resources, a 4-D development model—define, design, develop, and disseminate—was painstakingly followed. The study focused on Padang's acclaimed PGRI University of West Sumatra's teachers and students. Observation, interviews, and testing collected data. Field tests showed the training materials were practical and effective. This study found: First, the teaching materials perfectly matched student needs. Second, the design phase produced useful learning aids to supplement the teaching content. Finally, the development phase produced a comprehensive integration of cultural discourse-based teaching materials for the Education Profession course, anchored by a Discourse Analysis Approach, displaying excellent validity. Field experiments showed promising results: The integrated learning approach's success and students' responses confirmed the teaching materials' usefulness. Students' better learning outcomes showed the instructional materials' usefulness, even though lecturers' comprehension and application varied. Cultural dialogue in educational professional teaching materials enhances learning and creates a more inclusive and engaging educational environment, according to the findings. The research recommends continual adaptation and improvement of teaching approaches to ensure lasting educational impact, as success depended on learning process and demographic aspects. In conclusion, this research is a pioneering endeavour to improve the Educational Profession course through cultural discourse, bridging the gap between traditional teaching methods and independent learning pedagogies. The study emphasizes the necessity of culturally responsive and effective learning ecosystems, setting a precedent for future curriculum design and educational practises.